2021
DOI: 10.7150/ijbs.57168
|View full text |Cite
|
Sign up to set email alerts
|

Identification of low-dose radiation-induced exosomal circ-METRN and miR-4709-3p/GRB14/PDGFRα pathway as a key regulatory mechanism in Glioblastoma progression and radioresistance: Functional validation and clinical theranostic significance

Abstract: Glioblastoma is a central nervous malignancy with a very poor prognosis. This study attempted to explore the role of exosomes induced by low-dose radiation-induced (ldrEXOs) and ldrEXOs-derived circ-METRN in glioblastoma progression and radioresistance at the molecular, cellular, animal, and clinical levels. Results in the present study revealed that low-dose radiation stimulated the secretion of ldrEXOs which delivered high levels of circ-METRN. And circ-METRN-abundant ldrEXOs increased the expression of γ-H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…A recent study in glioblastoma cells showed that low-dose radiation triggered the secretion of exosomes containing high levels of circ-METRN, which in turn led to increased γH2AX [84]. This suggested the presence of an efficient DDRR process in glioblastoma cells.…”
Section: Circrnas As Regulators Of Ddrr Network Components and Genotoxic Stress In Cancermentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study in glioblastoma cells showed that low-dose radiation triggered the secretion of exosomes containing high levels of circ-METRN, which in turn led to increased γH2AX [84]. This suggested the presence of an efficient DDRR process in glioblastoma cells.…”
Section: Circrnas As Regulators Of Ddrr Network Components and Genotoxic Stress In Cancermentioning
confidence: 95%
“…This suggested the presence of an efficient DDRR process in glioblastoma cells. Circ-METRN was found to be responsible for tumor progression and resistance to treatment, hence exhibiting an oncogenic function through deregulation of the DDRR [84]. Another study on exosomes investigated the biology of exosomal circ-DB (circ-deubiquitination, hsa_circ_0025129), which is reciprocally related to miR-34 and negatively associated with the DNA repair player USP7 in hepatocellular carcinoma patients [85].…”
Section: Circrnas As Regulators Of Ddrr Network Components and Genotoxic Stress In Cancermentioning
confidence: 99%
“…Wang et al uncovered that low-dose radiation was able to induce the secretion of exosomes rich in circ-METRN. The increased circ-METRN upregulated DNA damage molecule γ-H2AX expression, but γ-H2AX level returned to normal at 24 h, indicating enhanced DNA damage repair process in radioresistant glioblastoma cells [ 167 ]. Moreover, in cisplatin-resistant GC, the PI3K/AKT pathway, which positively regulates BRCA1 expression, can be activated by circAKT3 [ 141 , 168 ].…”
Section: Circrnas and Cancer Therapeutic Resistancementioning
confidence: 99%
“…Moreover, exosome-derived circ-HIPK3 can promote TMZ-resistant GBM cell growth and TMZ resistance by modulating the miR-421/ZIC5 axis and participating in intercellular communication between GBM cells [ 102 ]. Low-dose radiation stimulates GBM cells to secrete circ-METRN-rich SEVs, and circ-METRN enhances glioblastoma progression and radioresistance by regulating the miR-4709-3p/GRB14/PDGFRα pathway [ 103 ]. Circ-0072083 in TMZ-resistant GBM tissues and cells Expression was significantly increased in both TMZ-resistant GBM tissues and cells.…”
Section: The Roles Of Texs In Chemoresistancementioning
confidence: 99%